Vasomodulation of peripheral blood flow by focused ultrasound potentiates improvement of diabetic neuropathy. Issue 1 (17th March 2020) - Tan, Joo-Shin; Lin, Chou-Ching; Chen, Gin-Shin
Abstract : Objective: Effective treatment methods for diabetic peripheral neuropathy are still lacking. Here, a focused ultrasound (FUS) technique was developed to improve blood flow in diabetic peripheral vessels and potentially treat diabetic peripheral neuropathy. Research design and methods: Male adult Sprague-Dawley rats at 4 weeks poststreptozotocin injections were adopted as models for diabetic neuropathic rats. For single FUS treatment, blood perfusion in the skin of the pad of the middle toe was measured before, during, and after the medial and lateral plantar arteries were treated by FUS. For multiple FUS treatments, blood perfusion measurements, von Frey and hot plate testing and nerve conduction velocity measurements were performed before ultrasonic treatment on the first day of each week, and the microvascular and neural fiber densities in the pad of the toe were measured on the first day of the last week. Results: The blood perfusion rate significantly increased for 7–10 min in the control and neuropathic rats after a single ultrasound exposure. Multiple ultrasound treatments compared with no treatments significantly increased blood perfusion at the second week and further enhanced perfusion at the third week in the neuropathic rats. Additionally, the paw withdrawal force and latency significantly increased from 34.33±4.55 g and 3.96±0.25 s at the first week to 39.10±5.02 g and 4.77±0.71 s at the second week and to 41.13±2.57 g and 5.24±0.86 s at the third week, respectively. The low nerve conduction velocity in the diabetic rats also improved after the ultrasound treatments. Additionally, ultrasound treatments halted the decrease in microvessel and neural fiber densities in the skin of the diabetic toes. Histologic analysis indicated no damage to the treated arteries or neighboring tissue. Conclusions: FUS treatment can increase upstream arterial blood flow in diabetic feet, ameliorate the decrease in downstream microvessel perfusion and halt neuropathic progression.